MULTIFACTOR RELATIONSHIP OF PHYSICAL ACTIVITY WITH OTHER RISK FACTORS FOR CORONARY HEART DISEASE - Rajabova , R.Sh.; Nurillaeva , N.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
The importance of physical inactivity as a health problem is constantly growing, since insufficient physical activity (FA) is a proven risk factor (RF) for the development of a number of chronic noncommunicable diseases (CNCDs) and their complications. A significant reduction in total cholesterol, lowdensity lipoprotein cholesterol and assign was observed in both groups under the influence of individually selected constant physical activity. HDL cholesterol levels were significantly increased in both groups. Calculation of physical activity in relation to risk factors for coronary artery disease with hypertension according to noninvasive research methods, taking into account the place of residence, lifestyle in real conditions and the possibilities of primary health care, should receive a full assessment and have a positive effect on the course of the underlying disease, improving the quality of life of patients